Multiparametric MRI study of ALS stratified for the C9orf72 genotype - HARDIMAN, ORLA; PENDER, NIALL; MCLAUGHLIN, RUSSELL (My University, 2013)
Objective: To describe the patterns of cortical and subcortical changes in amyotrophic lateral sclerosis (ALS) stratified for the C9orf72 genotype. Methods: A prospective, single-center, single-protocol, gray and white matter magnetic resonance case-control imaging study was undertaken with 30 C9orf72 -negative patients with ALS, 9 patients with ALS carrying the C9orf72 hexanucleotide repeat expansion, and 44 healthy controls. Tract- based spatial statistics of multiple white matter diffusion parameters, cortical thickness measure- ments, and voxel-based morphometry analyses were carried out. All patients underwent comprehen- sive genetic and neuropsychological profiling. Results: A congruent pattern of cortical and subcortical involvement was identified in those with the C9orf72 genotype, affecting fusiform, thalamic, supramarginal, and orbitofrontal regions and the Broca area. White matter abnormalities in the C9orf72 -negative group were relatively confined to corticospinal and cerebellar pathways with limited extramotor expansion. The body of the corpus callosum and superior motor tracts were affected in both ALS genotypes. Conclusions: Extensive cortical and subcortical frontotemporal involvement was identified in associ- ation with the C9orf72 genotype, compared to the relatively limited extramotor pathology in patients with C9orf72 -negative ALS. The distinctive, genotype-specific pathoanatomical patterns are con- sistent with the neuropsychological profile of the 2 ALS cohorts. Our findings suggest that previously described extramotor changes in ALS could be largely driven by those with the C9orf72 genotype
PUBLISHED
Keywords: amyotrophic lateral sclerosis (ALS); amyotrophic lateral sclerosis (ALS)